2007
DOI: 10.1111/j.1525-1438.2007.00872.x
|View full text |Cite
|
Sign up to set email alerts
|

Notch1 induces cell cycle arrest and apoptosis in human cervical cancer cells: involvement of nuclear factor kappa B inhibition

Abstract: Notch signaling can serve as a tumor suppressor or tumor promoter in the same kind of cancer, such as human papillomavirus-positive cervical cancer cells. However, the exact mechanisms remain poorly characterized. Our studies demonstrated that constitutively overexpressed active Notch1 via stable transfection with exogenous intracellular domain of Notch1 (ICN) resulted in growth inhibition of the human cervical cancer cell line HeLa by inducing G(2)-M arrest and apoptosis. Moreover, the growth inhibition was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 33 publications
2
36
0
Order By: Relevance
“…The GSI L-685, 458 can dose-dependently inhibit the growth of human tongue carcinoma cells by inducing G 0 -G 1 cell cycle arrest and apoptosis (Yao et al, 2007). However, the exact mechanism of action of GSIs in the Tca8113 cells has not been exactly revealed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GSI L-685, 458 can dose-dependently inhibit the growth of human tongue carcinoma cells by inducing G 0 -G 1 cell cycle arrest and apoptosis (Yao et al, 2007). However, the exact mechanism of action of GSIs in the Tca8113 cells has not been exactly revealed.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of Notch-1 in mammalian epithelial carcinoma has been well studied in mouse models and human carcinoma (Farnie and Clarke, 2007;Yao et al, 2007;Liu et al, 2008). Not only is over-expression of Notch detected in some epithelial derived carcinoma such as mammary, prostate and so on, but truncated NICD protein can induce carcinogenesis in vitro (Capobianco et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the Bcl-2 protein expression protects cells from apoptosis (14). However, the down-regulation of Bcl-2 was observed in Notch1-overexpressed cells (25). Because endothelial-expressed Jagged1 can activate Notch in adjacent VSMc (17), we therefore infer that suppressing Jagged1 in the Ecs may prevent Notch activation in adjacent VSMcs and cause up-regulation of Bcl-2 expression.…”
Section: Discussionmentioning
confidence: 91%
“…Among the Notch Pathways, Notch-1 and Myc (a well studied oncogene) expression are positively correlated by immunostaining in 38% of examined human breast carcinomas (9). Notch-1 cross-talk has also been reported with other major cell growth and apoptotic regulatory pathways through modulating the activity of the transcription factor, for example, nuclear factor-κ B (NF-κB) (10). The existing evidence led us to hypothesize that Notch signaling may be a potential therapeutic target for human breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…tiation in different organisms and cell types. It was reported that there is cross-talk between these two pathways in human cervical and pancreatic cancer and that Notch signaling may be the upstream regulator (10,12). We hypothesized that down-regulation of the downstream effects of Notch-1 could be related to the activity of the NF-κB pathway in human breast cancer.…”
Section: Sirna-mediated Down-regulation Of Notch-1 Inhibits Cell Growmentioning
confidence: 99%